Interobserver Variability in the Differential Diagnosis of Benign Bone Tumors and Tumor-like Lesions - Scheitza, P.; Uhl, M.; Hauschild, O.; Zwingmann, J.; Bannasch, H.; Kayser, C.; Südkamp, N. P.; Herget, G. W. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: The interobserver-variability of radiological diagnosis of benign bone tumors (BBT) and tumor-like lesions (TLL) was examined in order to identify difficult-to-diagnose entities, to examine the frequency of advanced diagnostics and to describe the number of interdisciplinary tumor center diagnoses (IDT) in comparison with diagnoses upon referral (ED) and radiologists´ diagnoses (RD).Materials and Methods: We retrospectively reviewed 413 patients with 272 BBT and 141 TLL, classified either histologically or through interdisciplinary consultation. Discrepancies between groups were analyzed and rates of additional imaging and biopsy to establish diagnosis were assessed.Results: In BBT the number of identical radiological diagnoses was 56 (ED) and 81 % (RD) compared to the IDT, while in the latter additional imaging were obtained in 30 % cases. In 21 % (12 % to establish diagnosis) BBT were biopsied, the ED matching the histology 40 %, the RD 60 % and the IDT 76 % of the time. For TLL diagnosed through radiology, ED and RD matched IDT 31 % and 61 % of the time, with additional imaging being obtained in 21 % of cases (IDT). In 36 % (27 % to establish diagnosis) biopsy was performed, with histological diagnosis matching the IDT, RD and ED in 51, 27 and 20 %. Diagnostic challenges were apparent in enchondromas, non-ossifying fibromas (NOF), solitary (SBC) and aneurysmal bone cysts (ABC). Ganglia can be misinterpreted as a tumor.Conclusions: Establishing a definitive diagnosis for BBT and TLL can be challenging with the latter posing greater difficulties. An interdisciplinary approach involving radiologists, orthopedics and pathologists was found to improve diagnostic accuracy.Key Points:• Benign bone tumors (BBT) and tumor-like lesions (TLL) present a diagnostic challenge, while enchondroma, NOF, SBC and ABC were difficult to diagnose, and ganglia can be misinterpreted as a tumor• Additional imaging studies were required for diagnosis in 29 % and 21 % of cases for BBT and TLL, respectively, biopsies in 12 % of cases for BBT and 27 % for TLL• Sound diagnoses can be made through interdisciplinary case discussion, while reducing the risk of overtreatmentCitation Format:• Scheitza P, Uhl M, Hauschild O et al. Interobserver Variability in the Differential Diagnosis of Benign Bone Tumors and Tumor-like Lesions. Fortschr Röntgenstr 2016; 188: 479 – 487
Keywords: benign bone tumor; tumor-like lesions; interobserver-variability; differential diagnosis